The treatment of tuberculosis in the upper thoracic spine using the small incision technique through the third rib - Ma, Jibin; Zhang, Zepei; Lan, Jie; Tian, Jiwei; Chen, Fulin; Miao, Jun (Frontiers in Surgery, 2023)
The complex anatomical structure of the upper thoracic spine makes it challenging to achieve surgical exposure, resulting in significant surgical risks and difficulties. Posterior surgery alone fails to adequately address and reconstruct upper thoracic lesions due to limited exposure. While the anterior approach offers advantages in fully exposing the anterior thoracic lesions, the surgical procedure itself is highly intricate. Although there exist various anterior approaches for the upper thoracic spine, the incidence of upper thoracic spine lesions is relatively low.Consequently, there are limited reports on the treatment and reconstruction of upper thoracic spine lesions using the third rib small incision approach in the context of upper thoracic tuberculosis.We collected data from four patients with upper thoracic tuberculosis who were admitted to our department between July 2017 and November 2022. The treatment for upper thoracic tuberculosis involved utilizing the third rib small incision approach, which included two cases of thoracic 3-4 vertebral tuberculosis, one case of thoracic 4 vertebral tuberculosis, and one case of thoracic 5 vertebral tuberculosis.Among the patients, three were positioned in the left lateral position, while one was positioned in the right lateral position. Prior to admission, all four patients received a two-week course of oral medication, consisting of isoniazid, rifampicin, pyrazinamide, and ethambutol. After the surgical procedure, they continued receiving anti-tuberculosis treatment for a duration of 12 months.The average duration of the surgical procedure was 150 minutes, with an average blood loss of 500ml. One patient exhibited symptoms of brachial plexus injury, which gradually improved after careful observation. All patients experienced primary wound healing, and no complications such as pulmonary infection, respiratory failure, or other adverse events were observed. Additionally, one patient showed elevated transaminase levels, leading to a modification in the anti-tuberculosis drug regimen from quadruple therapy to triple therapy.The treatment of upper thoracic tuberculosis through the third rib small incision technique is a very good surgical approach, which has the advantages of safety and effectiveness.